4x-2+9x+1=90

Simple and best practice solution for 4x-2+9x+1=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-2+9x+1=90 equation:


Simplifying
4x + -2 + 9x + 1 = 90

Reorder the terms:
-2 + 1 + 4x + 9x = 90

Combine like terms: -2 + 1 = -1
-1 + 4x + 9x = 90

Combine like terms: 4x + 9x = 13x
-1 + 13x = 90

Solving
-1 + 13x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 13x = 90 + 1

Combine like terms: -1 + 1 = 0
0 + 13x = 90 + 1
13x = 90 + 1

Combine like terms: 90 + 1 = 91
13x = 91

Divide each side by '13'.
x = 7

Simplifying
x = 7

See similar equations:

| y(x^2+7)+9(x^2+7)= | | -7-9=7x+9x-24x | | 6x-(2x-1)(2x+1)=2-(3+2x) | | -23.1/2.1= | | 1/8-3/20= | | -4.2(55)= | | 21-9=b | | 2/2x-5=3x+1 | | 6x+2(x+6)=23 | | 3-8t=48+t | | 23.1/-5..5= | | 3/2x-5=7 | | 2c+16/4=7 | | 2(-4x+3)=-x+27 | | 4d=2.50d | | (4x+x+7)/(x-4) | | 79.50=45-d | | -4x+1=4x-15 | | (x-4)/(x-8) | | x-58=7/8 | | -4.2(-5.5)= | | 25=-10 | | 97=-8a+1 | | -25=-10 | | 1,1/4*3/4= | | 3x+7-9=2(8-5) | | -3(3x-1)+4x=x+33 | | 11/4*3/4= | | 1/2(6x-8)=41 | | 72=18+x | | Y(x^7+2)+8(x^7+2)= | | 4=-10 |

Equations solver categories